Rosa and the pine/Rosa y el pino - Holmes, Maia, author; Peirce, Erika, illustrator; Fulladolsa, Ana Cristina, translator; Colorado State University, publisher (Colorado State University. Libraries, 2025)
Follow the story of Rosa, the mountain pine beetle, as she goes through her life cycle in the forests of the Rocky Mountains. Readers will learn all about how mountain pine beetles find pine trees to lay their eggs and how they serve as an important part in the ecosystem. Written and illustrated by entomologists (insect scientists) and translated by a plant pathologist (plant disease scientist).

Sigue la historia de Rosa, escarabajo del pino de montaña, mientras pasa por suciclo de vida en los bosques de las Montañas Rocosas. Los lectores aprenderán todo sobre cómo los escarabajos del pino de montaña encuentran pinos para poner sus huevos y como sirven cómo una parte importante en el ecosistema. Escrito e ilustrado por entomólogos (cientificas de insectos) y traducido por una pataloga de plantas (cientifica de enfermedades de plantas).
Rosa y el pino
College of Agricultural Sciences/Department of Agricultural Biology, Warner College of Natural Resources/Department of Forest and Rangeland Stewardship. Illustrations by Dr. Erika Peirce, translations by Ana Cristina Fulladolsa.
Text in both English and Spanish.
Keywords: children